Penyuluhan Hukum Tentang Pinjaman Online Di Komplek Perumahan Unand, Kelurahan Padang Besi Kecamatan Lubuk Kilangan Kota Padang - Marwenny, Elwidarifa; Somaliagustina, Desi; Fauzi, Engrina; Hamiwati, Hamiwati; Syafwar, Roby; Wahyuni, Sry; Dermawan, Andika; Alfitrianti, Nia; Citra, Helfira (Jurnal Pengabdian Masyarakat Dharma Andalas, 2024)
Community Service Activities that will be carried out by the Lecturer Team of the Dharma Andalas University Law Study Program will be accomplished in the form of law counseling related to Online Loans. This is intended to socialize to the public about legal online loans and vice versa. It is because the illegal online loans are very widespread and disturbing to the public because debt collectors who collect loans terrorize their victims. Law counseling was provided in one of the sub-districts in Padang City due to the large number of complaints from the people who were caught in online loans where the relevant task force received 8,991 complaints related to illegal loan until October 2023, so that the public needed to be given an understanding regarding to loan money, both legal and illegal, and the impacts from the perspective of law. This service is carried out by using a lecture method with laptop and LCD Projector in Padang City, particularly at the house of one of the residents in Unand Housing Complex, Padang Besi Village, Lubuk Kilangan District, Padang City. To measure their understanding, the participants were asked questions in the form of question-and-answer games.